2021
DOI: 10.3390/antiox10071144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phenolic Contents and Scavenging Activities of Miang Extracts Derived from Filamentous and Non-Filamentous Fungi-Based Fermentation Processes

Abstract: The study investigated the impact of the fermentation process on the phenolic contents and antioxidant and anti-inflammatory activities in extracts of Miang, an ethnic fermented tea product of northern Thailand. The acetone (80%) extraction of Miang samples fermented by a non-filamentous fungi-based process (NFP) and filamentous fungi-based process (FFP) had elevated levels of total polyphenols, total tannins, and condensed tannins compared to young and mature tea leaves. The antioxidant studies also showed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…Depending on the area of production, two different production processes have been established which include the filamentous fungi growth-based process (FFP) and the non-filamentous fungi growth-based process (NFP; Khanongnuch et al, 2017 ). In previous studies on the microbial community of Miang fermentation, lactic acid bacteria, Bacillus spp., yeasts, and filamentous fungi contributed to physico-chemical changes in Miang directly affected flavor and aroma, health-relevant bioactive compounds, and antioxidant activity of the Miang ( Unban et al, 2019 ; Abdullahi et al, 2021 ). The evolution of microorganisms associated with Miang fermentation has not yet been elucidated through in-depth studies.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the area of production, two different production processes have been established which include the filamentous fungi growth-based process (FFP) and the non-filamentous fungi growth-based process (NFP; Khanongnuch et al, 2017 ). In previous studies on the microbial community of Miang fermentation, lactic acid bacteria, Bacillus spp., yeasts, and filamentous fungi contributed to physico-chemical changes in Miang directly affected flavor and aroma, health-relevant bioactive compounds, and antioxidant activity of the Miang ( Unban et al, 2019 ; Abdullahi et al, 2021 ). The evolution of microorganisms associated with Miang fermentation has not yet been elucidated through in-depth studies.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds, which are natural antioxidants, have markedly generated interest in Miang production due to their potential beneficial effects on humans [ 3 , 4 , 26 ]. Interestingly, the MF-broth residual byproduct is similar to the extraction content of fermented leaves with water during the anaerobic fermentation, which causes the water-soluble phenolic compounds to be solubilized after release from the Miang leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant activity was based on 1,1-diphenyl-2-picrylhydrazyl (DPPH) (Sigma-Aldrich, St. Louis, MO, USA) free radical assay [ 26 ]. Briefly, 100 μL of diluted sample in DI water (10 μL/mL) was mixed with 400 μL of 0.15 mM DPPH in 80% methanol and incubated in the dark at ambient temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al found that lovastatin produced by monascus fermentation of pu-erh tea can induce neutrophil apoptosis by phosphorylation of ERK/AKT and reduce neutrophil recruitment to inflammatory sites, thereby reducing inflammation in zebrafish ( 77 ). In addition, Assam tea after fungal fermentation, compared with unfermented tea, microbial biological conversion of phenol makes total polyphenol, total tannin content in the fermented tea enhancement and enrichment of condensed tannins, thus as a target, the function of the bioactive ingredients in anti-inflammation mediated diseases such as cancer and cardiovascular disease found in the corresponding application ( 78 ). Moreover, Villarreal-soto et al studied the bioactivity of extracts from black tea fermented by kombucha bacteria.…”
Section: Changes Of Biological Activity In Tea After Microbial Fermen...mentioning
confidence: 99%